EFEKTIVITAS PENGGUNAAN MEDIA PERMAINAN CONGKLAK PADA PEMBELAJARAN OPERASI HITUNG BAGI SISWA KELAS AWAL SEKOLAH DASAR - Umi Musaropah; Nur Ayu Zita Sari; Toto Hermawan; Muhammad Nasruddin (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan Universitas Cokroaminoto Yogyakarta, 2022)
This research is motivated by the need for a combination of games in every lesson that is taught, especially learning mathematics. So testing the effectiveness of the use of Congklak Game Media in Learning Operations Counting Addition and Subtraction of Numbers in Class 1 students of SDN Surodadi 2 Ponjong Gunungkidul was carried out quantitatively. In this study obtained (RHO) observation = 0.826, while (RHO) table in the significance level of 5% = 0.576 and in the significance level of 5% = 0.708, it can be seen that (RHO) observation (0.826) > (RHO) tables (0.576) and (0.708). Thus, with N = 12 and a significance level of 5% and 1%, it can be concluded that there is a significant positive correlation between the use of Congklak Game Media and Learning Operations Counting Addition and Subtraction of Numbers in Class 1 SDN Surodadi II Ponjong Gunungkidul.